1991
DOI: 10.1111/j.1464-5491.1991.tb02155.x
|View full text |Cite
|
Sign up to set email alerts
|

Renal Functional Reserve in Diabetic Patients without Clinical Nephropathy: Comparisons with Renal Morphology

Abstract: The acute effect of a protein loading test (1.5 g kg-1) on glomerular filtration rate (GFR) was examined in 10 Type 1 diabetic patients without clinical nephropathy to evaluate the renal functional reserve. GFR was measured before (baseline) and after (test) ingestion of the protein load. Two groups of diabetic patients were distinguished: those who exhibited normal renal reserve equal to that in healthy individuals (change in GFR 35 +/- 17 (+/- SD)%) and those who had no renal reserve (change in GFR -20 +/- 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…In a renal disease, RFR maintains the whole organ GFR but when residual nephrons can no longer compensate, deterioration in GFR appears [13]. A previous study evaluated RFR in type I diabetics without clinical nephropathy and suggested its measurement can be an important tool for the diagnosis of latent diabetic nephropathy [14]. Livi et al studied RFR in 21 SSc patients with normal renal function using creatinine and para-aminohippurate clearance for GFR and effective renal plasma flow calculation, respectively, and calculated total renal vascular resistance before and after an intravenous amino acid load [15,16].…”
Section: Introductionmentioning
confidence: 97%
“…In a renal disease, RFR maintains the whole organ GFR but when residual nephrons can no longer compensate, deterioration in GFR appears [13]. A previous study evaluated RFR in type I diabetics without clinical nephropathy and suggested its measurement can be an important tool for the diagnosis of latent diabetic nephropathy [14]. Livi et al studied RFR in 21 SSc patients with normal renal function using creatinine and para-aminohippurate clearance for GFR and effective renal plasma flow calculation, respectively, and calculated total renal vascular resistance before and after an intravenous amino acid load [15,16].…”
Section: Introductionmentioning
confidence: 97%
“…In the literature there is considerable inconsistency in reported RFR values in patients with Type 1 diabetes. In two studies where kidney biopsies were performed, negative RFR was found in patients with histological signs of glomerulosclerosis [1] and in patients with hilar glomerular lesions with expanded mesangium [2]. In both studies it was suggested that negative RFR precedes other subclinical manifestations of diabetic nephropathy.…”
Section: Discussionmentioning
confidence: 96%
“…Some patients with Type 1 diabetes mellitus have decreased renal functional reserve (RFR) before they develop incipient diabetic nephropathy [1,2] as characterised by microalbuminuria. At a very early stage of diabetic nephropathy, reduced endothelial sensitivity of renal afferent arterioles to nitric oxide occurs [3], possibly caused by reactive oxygen species [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…protein load) due to a reduced capacity of renal autoregulation (22)(23)(24)(25). These functional changes, that could be also encountered in diabetic patients, were found to be associated with or precede microalbuminuria and glomerular lesions (26,27). Indeed, proteinuria is not considered to be a ''normal'' physiological process of aging also in cases when the development of a persistent proteinuria increases with age, due to the higher prevalence of diabetes, hypertension and paraproteinemias in the elderly (28).…”
Section: Discussionmentioning
confidence: 97%